2022
DOI: 10.3389/fsurg.2022.930215
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Poor Defecation Habits and Postoperative Hemorrhoid Recurrence

Abstract: BackgroundThe relationship between hemorrhoid recurrence and poor defecation habits is poorly understood. This study aimed to analyze the effects of poor defecation habits on postoperative hemorrhoid recurrence.Materials and MethodWe performed a retrospective study on 1,162 consecutive patients who underwent a surgical procedure for hemorrhoids at the Sixth Affiliated Hospital of Sun Yat-Sen University from December 2016 to May 2020. All patients were followed for 12 months post-operatively. Patients were moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Amongst patients undergoing haemorrhoidectomy, a Saudi Arabian study found 24.2% had obstructed defaecation syndrome and this was shown to have a negative correlation with postoperative patient satisfaction [13]. A Chinese study also showed that a higher obstructed defaecation score was significantly associated with recurrence of haemorrhoids postoperatively and less satisfaction with surgery [14]-both studies supporting the importance of treating the underlying defaecatory disorder, along with its consequent haemorrhoids.…”
Section: The Symptom Complex and Associated Problemsmentioning
confidence: 98%
“…Amongst patients undergoing haemorrhoidectomy, a Saudi Arabian study found 24.2% had obstructed defaecation syndrome and this was shown to have a negative correlation with postoperative patient satisfaction [13]. A Chinese study also showed that a higher obstructed defaecation score was significantly associated with recurrence of haemorrhoids postoperatively and less satisfaction with surgery [14]-both studies supporting the importance of treating the underlying defaecatory disorder, along with its consequent haemorrhoids.…”
Section: The Symptom Complex and Associated Problemsmentioning
confidence: 98%